1993
DOI: 10.1021/ef00037a010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of N-methyl-2-pyrrolidinone in coal extracts by TGA-FTIR

Abstract: JV-Methyl-2-pyrrolidinone (NMP) is widely used in coal extraction. It has been shown that NMP is strongly retained in coal extracts and the retained NMP affects the character of the extracts. In order to calculate the actual extraction yield and understand the interaction between NMP and coal, the amount of NMP retained by its coal extracts must be quantified. TGA-FTIR has been applied to the quantitative analysis of NMP. Neutral aluminum oxide with 4.74% NMP added was used as a standard, and a linear calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This mass loss is attributed to the loss of NMP during the thermal process. It has been shown that NMP polymerizes when used at elevated temperatures in air [31,32]. This polymerized NMP has been revealed to lose mass in a similar range as that reported in the TGA curves ( Figure 3) in a nitrogen environment [33].…”
Section: % Remaining Of Pristine Cnt −supporting
confidence: 65%
“…This mass loss is attributed to the loss of NMP during the thermal process. It has been shown that NMP polymerizes when used at elevated temperatures in air [31,32]. This polymerized NMP has been revealed to lose mass in a similar range as that reported in the TGA curves ( Figure 3) in a nitrogen environment [33].…”
Section: % Remaining Of Pristine Cnt −supporting
confidence: 65%
“…43 NMP has also been suggested to causes cleavage of carbon–oxygen bonds in coals when used under refluxing conditions. 39 In these reactions, a hydroperoxide is thought to be an intermediate in the reaction of NMP and oxygen-yielding N -methylsuccinimide. 40 In our experiments, pure NMP changes color from clear to brown when refluxed under atmospheric oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…4. The broad absorption band at 3440 and 3454 cm -1 in the case of both coal samples and frequencies at 3429, 3435, 1655 and 1661 cm -1 in pure NMP and permeate, were observed due to N-H stretching vibration (Cai and Smart 1993). Two stronger bands 2933 and 2935 cm -1 were observed in pure NMP due to CH 3 -CH 2 vibrations.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 88%